2015
DOI: 10.1126/science.aab1586
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the algal dimethyl sulfide–releasing enzyme: A missing link in the marine sulfur cycle

Abstract: Algal blooms produce large amounts of dimethyl sulfide (DMS), a volatile with a diverse signaling role in marine food webs that is emitted to the atmosphere, where it can affect cloud formation. The algal enzymes responsible for forming DMS from dimethylsulfoniopropionate (DMSP) remain unidentified despite their critical role in the global sulfur cycle. We identified and characterized Alma1, a DMSP lyase from the bloom-forming algae Emiliania huxleyi. Alma1 is a tetrameric, redox-sensitive enzyme of the aspart… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
259
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 221 publications
(269 citation statements)
references
References 42 publications
2
259
0
1
Order By: Relevance
“…A possible direct release of DMS by intracellular or extracellular DMSP-lyase activity of algae (Niki et al, 2000;Stefels, 2000;Alcolombri et al, 2015) is also disregarded. To the best of our knowledge, no studies as of yet have shown that diatoms, the dominant group of the bottom-ice algal community, possess or use DMSP-lyases.…”
Section: Limitations Of the Present Studymentioning
confidence: 99%
“…A possible direct release of DMS by intracellular or extracellular DMSP-lyase activity of algae (Niki et al, 2000;Stefels, 2000;Alcolombri et al, 2015) is also disregarded. To the best of our knowledge, no studies as of yet have shown that diatoms, the dominant group of the bottom-ice algal community, possess or use DMSP-lyases.…”
Section: Limitations Of the Present Studymentioning
confidence: 99%
“…Its primary source is the enzymatic cleavage of dimethylsulfoniopropionate (DMSP), a multifunctional osmolyte that accumulates at high (hundred millimolar) intracellular concentrations in some phytoplankton, especially haptophytes, dinoflagellates and some picoeukaryotes (Stefels et al, 2007). DMSP cleavage is catalyzed by a wide diversity of enzymes, called DMSP lyases, produced by some phytoplankton (Alcolombri et al, 2015) and bacteria (Curson et al, 2011). Breakage of phytoplankton cells through zooplankton grazing, viral attack and autolysis releases DMSP to the algal boundary layer and the dissolved phase and enhances DMS production (Simó, 2004;Stefels et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Bacterial production of DMS is not the sole pathway bolstering reservoirs of DMS in marine waters: certain species of autotrophic phytoplankton can also directly cleave DMSP into DMS. Although the particular enzymatic reactions that govern DMSP breakdown are not fully characterized (Todd et al, 2007), most reactions are attributed to DMSP lyases (Alcolombri et al, 2015;Schafer et al, 2010;Stefels et al, 2007). What controls the contribution of either process (autotrophic or heterotrophic DMSP to DMS conversion) in fuelling DMS stocks remains unclear but appears to vary extensively (Lizotte et al, 2012).…”
mentioning
confidence: 99%